African descent women teachers in the Caribbean region of colombia: A case study - Martinez Carazo, Piedad Cristina; Lago De Vergara, Diana Elvira; Buelvas Martínez, Armando (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this paper is to delve into the State policies around ethno-education, the women teachers and their classroom practices, through an in-depth interview conducted with an Afro-Caribbean Colombian teacher. In addition, it was carried out a review of legal and empirical background in the field of ethno-education by means of the case study methodology. The results demonstrate that the existence of a State policy on ethno-education, despite the lack of resources for its implementation, has constituted an orientation guide for the teacher, object of this study, whose teaching practices have played a key role in dynamising the teaching process as well as consolidating the identity shared by students, parents and her very own Afro-descendant community. Likewise, her traditions; customs; values; training; environmental resources; oral tradition; and the students´ needs, have influenced her teaching practice focused on the re-significance of her ethnicity, the pursuit of peace and social transformation in the post-conflict period experienced in the Caribbean Region of Colombia.